A new solar wind‐driven global dynamic plasmapause model: 1. Database and statistics. Issue 7 (6th July 2017) - Zhang, Xiao‐Xin; He, Fei; Lin, Rui‐Lin; Fok, Mei‐Ching; Katus, Roxanne M.; Liemohn, Michael W.; Gallagher, Dennis L.; Nakano, Shinya
Abstract: A large database, possibly the largest plasmapause location database, with 49, 119 plasmapause crossing events from the in situ observations and 3957 plasmapause profiles (corresponding to 48, 899 plasmapause locations in 1 h magnetic local time (MLT) intervals) from optical remote sensing from 1977 to 2015 by 18 satellites is compiled. The responses of the global plasmapause to solar wind and geomagnetic changes and the diurnal, seasonal, solar cycle variations of the plasmapause are investigated based on this database. It is found that the plasmapause shrinks toward the Earth globally and a clear bulge appears in the afternoon to premidnight MLT sector as the solar wind or geomagnetic conditions change from quiet to disturbed. The bulge is clearer during storm times or southward interplanetary magnetic field. The diurnal variations of the plasmapause are most probably the result of the difference between the magnetic dipole tilt and the Earth's spin axis. The seasonal variations of the plasmapause are characterized by equinox valleys and solstice peaks. It is also found that the plasmapause approaches the Earth during high solar activity and expands outward during low solar activity. This database will help us study and understand the evolution properties of the plasmapause shape and the interaction processes of the plasmasphere, the ring current, and the radiation belts in the magnetosphere. Key Points: The largest currently available plasmapause location database is compiled based on observations from 18 satellites from 1977 to 2015 This database reveals the responses of the global plasmapause locations to solar wind and geomagnetic changes The plasmapause locations exhibit clear MLT‐dependent diurnal, seasonal, and solar cycle variations